Estimating the Cost to U.S. Health Departments to Conduct HIV Surveillance. (November 2014) - Shrestha, Ram K.; Sansom, Stephanie L.; Laffoon, Benjamin T.; Farnham, Paul G.; Shouse, R. Luke; MacMaster, Karen; Hall, H. Irene
Objectives: HIV case surveillance is a primary source of information for monitoring HIV burden in the United States and guiding the allocation of prevention and treatment funds. While the number of people living with HIV and the need for surveillance data have increased, little is known about the cost of surveillance. We estimated the economic cost to health departments of conducting high-quality HIV case surveillance. Methods: We collected primary data on the unit cost and quantity of resources used to operate the HIV case surveillance program in Michigan, where HIV burden (i.e., the number of HIV cases) is moderate to high ( n =14, 864 cases). Based on Michigan's data, we projected the expected annual HIV surveillance cost for U.S., state, local, and territorial health departments. We based our cost projection on the variation in the number of new and established cases, area-specific wages, and potential economies of scale. Results: We estimated the annual total HIV surveillance cost to the Michigan health department to be 1, 286, 524 (87/case), the annual total cost of new cases to be 108, 657 (133/case), and the annual total cost of established cases to be 1, 177, 867 (84/case). Our projected median annual HIV surveillance cost per health department ranged from 210, 600 in low-HIV burden sites to 1, 835, 000 in high-HIV burden sites. Conclusions: Our analysis shows that a systematic approach to costing HIV surveillance at the health department level is feasible. For HIV surveillance, a substantial portion of total surveillance costs is attributable to maintaining established cases.